The Role of Green Marketing in Achieving Customer Loyalty: An Applied Study in Diyala General Company for Electrical Industries - Mahmood Hassan Jumah; Rahman Mahmood Shahaza; Sadiq Hussein Abdalhassan (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Adopting the concept of green marketing is an urgent necessity for business organizations, helping them achieve many benefits, such as conserving natural resources and not harming the environment and achieving customer satisfaction by providing safe and environmentally friendly products.This research tests the relationship linkage and effect between the green marketing and customer loyalty, it consisted of the research problem of the impact of green marketing in the achievement customer loyalty in Diyala public company for electrical industrial. A questionnaire was used in data collection depending on the distribution of (49) questionnaire to the research sample. Data were analyzed using (SPSS) program. Using a number of statistical tools for tests the research hypothesis. The research found set of conclusions, one of the most important thinks was, that there is a linkage and impact relation between green marketing, its variables (Waste concept cancellation, Product redesign, Clarity of the relationship between price and cost, Making profitable environmental orientation), and customer loyalty as a whole. The research came out with many suitable recommendations.